UPAYA MENINGKATKAN KETERAMPILAN ABAD 21 DENGAN MODEL INQUIRY LEVELS DALAM PEMBELAJARAN IPA - Herlina, Linlin (Bioed : Jurnal Pendidikan Biologi, 2019)
This study aim to describe 21st Century skills improvement through the Demand Level Learning Model. The formulation of the problem in this study is: can the Demand Level Learning Model improve 21st century skills? The Classroom Action Research (CAR) was conducted in two cycles. Each learning cycle consists of four sides, namely: (a) action planning; (b) action implementation (c) action observation; and (d) reflection. The subjects of this study were students of class VII C of SMP 7 Banjarsari, Ciamis Regency with a total of 22 students. Data analysis was performed during the study from the beginning to the end of the study. Based on the results of research and discussion, it can be concluded that there is an improvement in 21st century skills, namely critical thinking, communication skills (oral and written), leadership abilities, collaboration, adaptability, productivity and accountability capabilities, and the ability to access, analyze, and synthesize information.Keywords: 21st Century Skills, Inquiry Levels Model, Science Learning